Web-Based Counseling Technology Development with Object Oriented Framework - Agus Pamuji; Nasywa Nazifah (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2023)
The design and adjustment of information systems are presently undergoing a transformation following the particular problems they are intended to tackle. The objective of this paper is to elucidate the terminology employed in the development of an information system. In the past ten years, there has been a significant increase in the popularity of building information systems. There have been numerous suggestions offered, each exhibiting different attributes. The counselling information system hadÂ  made by using a method that focuses on organizing information clearly and simply. The main goal of this research is to find solutions to the problems and needs of creating new systems. Modelling in system development helps us use different modelling languages to solve problems. This starts with identifying issues using use case modelling languages, then simplifying problems with structured modelling, and finally creating communication patterns or interactions between objects using sequence diagrams. By designing this system, we have provided a means to comprehend the intricate nature of information systems, particularly when it comes to counselling information.